WROUGHT - Sigrithur, Anna; Penner, Joel (Cuizine, 2018)
These still images and video are excerpts from the short film Wrought (2018). Wrought is a hybrid natural history/art film which uses innovative timelapse scanner videography to capture up-close and macroscopic views of rotting material. The subject matter in the film encapsulates the three categories of rot which we have chosen to explore for their significance to human notions of purity, morality, and society: to spoil, to ferment and to decompose.